Present knowledge of modern technology and virtual computer reality to assess the angle of strabismus - Durajczyk, Magdalena; Grudzińska, Ewa; Modrzejewska, Monika (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
The article constitutes a review of studies about diagnosis of strabismus using advanced technology, the use of virtual reality as well as other applications of already well-known devices such as optical coherence tomography in the diagnosis of strabismus. Technological advances should shorten the examination time significantly and make the result independent of the investigator’s experience. The future of strabismic ophthalmology lies in the use of innovative equipment to enable objective, reliable and reproducible measurements of the type of muscle disorder.